2019
DOI: 10.1002/hep4.1345
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Institutional Factors and Long‐Term Survival Following Transjugular Intrahepatic Portosystemic Shunt

Abstract: Transjugular intrahepatic portosystemic shunt (TIPS) is a procedure designed to treat portal hypertension. Hospital teaching status is an institutional factor found to be predictive of outcomes following several complex procedures; however, its impact on outcomes following TIPS is unknown. The aim of this study was to determine the association between hospital teaching status and long‐term survival in patients with cirrhosis receiving TIPS. We performed a retrospective population‐based cohort study using linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…An American study in 2017 found that the risk of inpatient mortality was lower in hospitals performing ≥20 TIPS per year 22. Consistent with this study, a recent Canadian study found that outcomes improved with units performing a minimum of 10 procedures per year 23. With only seven units performing more than 10 procedures in Australia, there is a need to address centralisation versus decentralisation of services: the advantage of centralised provision of TIPS would provide expert care, high-level infrastructure, state-of-the-art diagnostic tests and therapies.…”
Section: Discussionsupporting
confidence: 52%
“…An American study in 2017 found that the risk of inpatient mortality was lower in hospitals performing ≥20 TIPS per year 22. Consistent with this study, a recent Canadian study found that outcomes improved with units performing a minimum of 10 procedures per year 23. With only seven units performing more than 10 procedures in Australia, there is a need to address centralisation versus decentralisation of services: the advantage of centralised provision of TIPS would provide expert care, high-level infrastructure, state-of-the-art diagnostic tests and therapies.…”
Section: Discussionsupporting
confidence: 52%
“…Additionally, there were units reporting a total number of procedures performed (elective and emergency) in a year of eight, raising the challenging question of numbers required for competency. A recent Canadian publication indicated that outcomes improved with units performing a minimum of 10 procedures per year 186. Furthermore, between 2006–2017, there was no clear evidence of an increase in emergency procedures, despite published evidence and recommendations.…”
Section: Service Delivery and Developmentmentioning
confidence: 99%
“…For complex TIPSS (thrombosed portal or hepatic veins, or previous transplant) it is recommended that these are performed in centres with >20 cases per annum and given the small numbers of outcome data and benchmarking, is difficult 187. Further evidence supports the need to ensure that centres wishing to start a TIPSS perform at least 10 procedures a year, regardless of whether the centre is a teaching hospital or not 186…”
Section: Service Delivery and Developmentmentioning
confidence: 99%
“…Covariates yielding a P-value of 0.1 on univariate analysis were fed into respective multivariable models. [28][29][30][31][32] P-values <0.05 were deemed statistically significant.…”
Section: Data Interpretation and Statistical Analysismentioning
confidence: 99%